2019
DOI: 10.1016/j.heliyon.2019.e01770
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wear parameters on friction performance of A356 aluminum – graphite/ granite particles reinforced metal matrix hybrid composites

Abstract: In this work aluminium-silicon alloy (A356) is strengthened with blends of granite and graphite particles using stir casting technique. Granite particulates, an industrial waste generated while cutting granite stones is used along with graphite particulates which has excellent lubricant properties. The reinforcements are mixed in different weight proportions, to base alloy at 2 and 4 weight percentages. Wear rate and friction for the fabricated composites and alloy is recorded during each sliding test The dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Previous research confirmed that AMC is a suitable composite for an extensive diversity of applications, since it is an excellent multifunctional lightweight material with remarkable properties; however, aluminum alloys are required to improve their wear resistance in high-performance tribological application because of their poor wear resistance and low hardness value [15]. Therefore, there is a high possibility of oscillation if these materials were joined by bolting or riveting, which might lead to sliding wear in some environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research confirmed that AMC is a suitable composite for an extensive diversity of applications, since it is an excellent multifunctional lightweight material with remarkable properties; however, aluminum alloys are required to improve their wear resistance in high-performance tribological application because of their poor wear resistance and low hardness value [15]. Therefore, there is a high possibility of oscillation if these materials were joined by bolting or riveting, which might lead to sliding wear in some environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in this study, the AA/W composite showed the least COF value which is 30.43% lower than the AA8090 alloy. Satyanarayana et al (2019) studied the wear performance of A356 aluminum-graphite/granite composite and reported that the addition of graphite and granite significantly reduced the wear and showed a lower COF value than that of A356 aluminum. This result is good in agreement with the results obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…However, the same variant also exhibited the highest COF, which is desired in terms of its application as a material used in the brake drum. Granite particulate—a waste generated while cutting granite stones—was an object of interest of Satyanarayana et al, who investigated its impact on the tribological performance of the aluminum-silicon alloy A356 (also with co-addition of graphite) [ 121 ]. The obtained results suggested that either reinforcement with sole granite (2 wt %) or with a combination of granite and graphite (4 and 2 wt %, respectively) contribute to a decrease in the value of COF as compared to neat A356 alloy.…”
Section: Industrial Waste Materialsmentioning
confidence: 99%